2004
DOI: 10.1152/ajpheart.00148.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of free radical outflow from an isolated muscle bed in exercising humans

Abstract: Incremental knee extensor (KE) exercise performed at 25, 70, and 100% of single-leg maximal work rate (WR(MAX)) was combined with ex vivo electron paramagnetic resonance (EPR) spectroscopic detection of alpha-phenyl-tert-butylnitrone (PBN) adducts, lipid hydroperoxides (LH), and associated parameters in five males. Blood samples were taken from the femoral arterial and venous circulation that, when combined with measured changes in femoral venous blood flow, permitted a direct examination of oxidant exchange a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
2
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 62 publications
(63 reference statements)
7
101
2
2
Order By: Relevance
“…It is known that acute exercise in hypoxia (Araneda et al 2005;Bailey et al 2001;Joanny et al 2001;Moller et al 2001;Pialoux et al 2006) and normoxia (Bailey et al 2001;Bailey et al 2004) increases oxidative stress compared to resting conditions. On the other hand, regular intermittent hypoxic training was leading to attenuated increases in lipid peroxidation and reduced plasma malondialdehyde due to mobilization of α-tocopherol compared with normoxic training (Bailey et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that acute exercise in hypoxia (Araneda et al 2005;Bailey et al 2001;Joanny et al 2001;Moller et al 2001;Pialoux et al 2006) and normoxia (Bailey et al 2001;Bailey et al 2004) increases oxidative stress compared to resting conditions. On the other hand, regular intermittent hypoxic training was leading to attenuated increases in lipid peroxidation and reduced plasma malondialdehyde due to mobilization of α-tocopherol compared with normoxic training (Bailey et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is known that exposure to altitude combined with exercise (Araneda et al 2005;Bailey et al 2001;Chao et al 1999;Pfeiffer et al 1999;Schmidt et al 2002), and even exposure to altitude in resting conditions (Bailey et al 2001), increases reactive oxygen species (ROS) levels/formation, especially in lung and blood. On the other hand, acute physical work per se is a contributor to oxidative stress where mitochondria represent the major source of free radicals (Bailey et al 2001;Bailey et al 2004;Sen 1995). Apart from excercise, additional stressors increase oxidative stress at altitude, such as exposure to ultra violet light, lack of dietary antioxidants, cold climate, increased xanthine oxidase activation and catecholamine production, as well as increased reductive stress and generation of free radicals through anoxia/reoxygenation (Askew 2002 (Horvath et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS formation in skeletal muscle following exercise has been demonstrated directly in animals (70,153) and indirectly in humans (15). In vitro, murine skeletal myotubes release IL-6 when exposed to oxidative stress in a NFB-dependent way (177).…”
Section: B Nfbmentioning
confidence: 99%
“…Specifically, vigorous or maximal exercise induced high levels of peroxidative damage, while moderate to low intensity exercise caused lower levels of damage. 35 Saiki et al 31 reported that following acute treadmill exercise, obese persons had greater elevations in serum hypoxanthine (a metabolite formed during vigorous exercise that may be involved in superoxide formation) than nonobese counterparts. While there was no direct oxidative biomarker in this study, the evidence suggests that obese persons had greater oxidative metabolic stress than nonobese persons.…”
Section: Obesity and Evidence Of Oxidant Stress In Humansmentioning
confidence: 99%